Just kidding : using humor effectively - Franzini, Louis R., 1941- (Rowman & Littlefield Publishers, 2012)
"For adults who enjoy humor and who would like to be funnier. It includes definitions of funniness and examples of both helpful and harmful humor. It describes the relevant comedic and psychological rules for making humor effective. The book points out the danger signs for offensive humor and how to make the decision to 'say it or stuff it.' Examples of successful and unsuccessful humor from comedians to politicians are used throughout to illustrate the many varieties of humor and how context and audience make a difference. Finally, a variety of fun exercises are offered to build the skills for effective humor making"--